Different tightening schemes in thread-drawing therapy and their effects on anal function recovery in patients with high simple anal fistula - Zhao, Pengfei; Wang, Lifang; Song, Qian; Yuan, Shili; Yang, Dongmei; Liu, Yao; Zhang, Tao (Frontiers in Physiology, 2025)
ObjectiveWe aimed to compare the effects of different tightening schemes in thread-drawing therapy on the recovery of anal function in patients with high simple anal fistulas after treatment.MethodsOne hundred patients with high simple anal fistulas who met the inclusion criteria were randomly divided into four groups of 25 patients each. All patients underwent low-level incision and high-level thread-drawing surgery. In the 1/5, 1/4, 1/3, and 1/2 groups, the rubber band cutting force was applied by tightening the surrounding muscle bundle to 1/5, 1/4, 1/3, and 1/2 of its circumference, respectively (using a graduated rubber band). Subsequent tightenings were also performed to the corresponding fractions of the circumference. The overall clinical efficacy, wound healing time, wound symptom score, anal function, and Wexner score were compared among the four groups.ResultsThe 1/5 group had the longest wound healing time, longer than those of the 1/4, 1/3, and 1/2 groups (p < 0.05). On the seventh postoperative day, the 1/2 group had a higher wound symptom score than the 1/5, 1/4, and 1/3 groups (p < 0.05). Three months after surgery, patients in the 1/5 group had higher resting anal canal pressure and maximum anal canal systolic pressure than the other three groups; the 1/4 and 1/3 groups had higher values than the 1/2 group (p < 0.05). One month and 3 months after surgery, patients in the 1/2 group had the highest Wexner scores, higher than those in the 1/5, 1/4, and 1/3 groups (p < 0.05).ConclusionTightening schemes of the 1/4 and 1/3 groups were found to be optimal as they resulted in less postoperative pain and minimal impact on anal function.